The feedback driven atomic scale Josephson microscope - Samuel D. Escribano; Víctor Barrena; David Perconte; Jose Antonio Moreno; Marta Fernández Lomana; Miguel Águeda; Edwin Herrera; Beilun Wu; Jose Gabriel Rodrigo; Elsa Prada; Isabel Guillamón; Alfredo Levy Yeyati; et al. (Nature Communications)
Abstract The ultimate spatial limit to establish a Josephson coupling between two superconducting electrodes is an atomic-scale junction. The Josephson effect in such ultrasmall junctions has been used to unveil new switching dynamics, study coupling close to superconducting bound states or reveal non-reciprocal effects. However, the Josephson coupling is weak and the sensitivity to temperature reduces the Cooper pair current magnitude. Here we show that a feedback element induces a time-dependent bistable regime which consists of spontaneous periodic oscillations between two different Cooper pair tunneling states (corresponding to the DC and AC Josephson regimes respectively). The amplitude of the time-averaged current within the bistable regime is almost independent of temperature. By tracing the periodic oscillations in the new bistable regime as a function of the position in a Scanning Tunneling Microscope, we obtain atomic scale maps of the critical current in 2H-NbSe2 and find spatial modulations due to a pair density wave. Our results fundamentally improve our understanding of atomic size Josephson junctions including a feedback element in the circuit and provide a promising new route to study superconducting materials through atomic scale maps of the Josephson coupling.